Cluster (Co3(CO)3([mu]2-CO)3([mu]3-C8H8))- as a ligand: xxperimental and theoretical study - Vinogradov, Mikhail M.; Wadepohl, Hubert (European journal of inorganic chemistry, 2017)
The cluster anion [Co3(CO)3(µ2-CO)3(µ3-C8H8)]- (2) reacts with fragments [(ring)M]+ and [(cod)M]+ to give the Co3M clusters (ring)MCo3(CO)3(µ3-CO)3(µ3-C8H8) (ring)M = CpFe (3a), Cp*Fe (3b), CpRu (4a), (C4Me4)Co (5) and (cod)MCo3(CO)3(µ3-CO)3(µ3-C8H8) M = Rh (6), Ir (7), respectively. However, 2 does not form stable complexes with [(Ph3P)M]+ species (M = Cu, Ag, Au), which was explained on the basis of DFT calculations by the inefficient overlap between the cluster and fragment orbitals. The structures of 3b and 5 were determined by X-ray diffraction.
Gesehen am 11.09.2018
Die komplette Formel im Titel steht in eckigen Klammern, die Zahlen sind tiefgestellt, der Bindestrich am Ende ist hochgestellt